Chronic calcified subdural hematoma masquerading as hemorrhagic extra-axial mass: A case report and brief review of the literature - Musharaf Khan, DO; Subtain Ali, MD; Joe T. Joseph, MD; Sanjay Bhatia, MBBS, MS, MBChB, MBA, FAANS, DABA; Dhairya A. Lakhani, MD (Radiology Case Reports)
Calcified chronic subdural hematoma (CCSDH) is a rare condition characterized by the accumulation of calcified blood between the dura mater and arachnoid membrane, typically following remote trauma. These lesions often present as space-occupying, extra-axial masses over the cerebral convexity and can mimic extra-axial tumors, such as calcified meningiomas. A 73-year-old male with a history of prostate cancer, hypertension, and hyperlipidemia presented with vision changes and mild papilledema. CT imaging revealed a hyperdense, heterogeneous mass with localized mass effect, while MRI suggested a calcified meningioma due to minimal enhancement and a Dural tail. Given the mass effect and neurological symptoms, surgical evacuation was performed, and intraoperative findings confirmed a chronic subdural hematoma. Postoperatively, the patient's symptoms improved, and imaging confirmed complete hematoma evacuation. This case highlights the challenges in diagnosing CCSDH, as it can closely resemble other conditions like meningiomas, emphasizing the need for careful radiological assessment and timely surgical intervention.